Generalized Fibonacci-Like Polynomials and Some Identities - Gupta, Yogesh; Singh, Mamta; Sikhwal, Omprakash (Global Journal of Mathematical Analysis, 2014)
The Fibonacci polynomials and Lucas polynomials are famous for possessing wonderful and amazing properties and identities. In this paper, Generalized Fibonacci-Lucas Polynomials is introduced and defined by with and. some basic identities established and derived by standard methods.Keywords: Fibonacci Polynomials, Lucas Polynomials, Generalized Fibonacci PolynomialsMSC: 2000: 11B37, 11B39